(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The results of the assessment of interventions in treating dementia in the elderly by non-medical methods combined with oriental medicament Ginkgo Biloba in Nghe An province. (2022-2023) Method: Research comparing pre-intervention and post-intervention, the uncontrolled intervention research method Results: Among 125 patients treated with non-drug intervention combined with Ginkgo Biloba herbal medicine, the rate of normal patients increased to 40% after 3 months and 60.8% after 6 months. Patients at mild levels decreased from 63.2% to 40% after 3 months and 26.2% after 6 months. Patients at moderate levels decreased from 30.4% to 16% after 3 months and 11.2% after 6 months. Patients at severe levels decreased from 6.4% to 4% after 3 months and 1.6% after 6 months. The average MMSE point increased from 19.6 ± 3.67, after 3 months of intervention 21.8 ± 3.79, after 6 months of intervention 23.3 ±. The difference was statistically significant (p < 0.001). The average ADL point increased from 4.59 ± 1.34, after 3 months, it increased to 4.87 ± 1.16; after 6 months, it increased to 5.29 ± 0.92, the difference was statistically significant (p < 0.05). The average IADL point increased from 2.38 ± 1.52, after 3 months of intervention, it increased to 3.13 ± 1.75, after 6 months of intervention, it increased to 4.16 ± 1.74, the difference was statistically significant (p < 0.05). Conclusion: Nonpharmacological interventions for dementia combined with the use of Ginkgo Biloba herbal medicine have shown good results.